The pregnant women’s experiences during the COVID-19 pandemic: a scoping review - Shelly Rodliah Rosyad; Yekti Satriyandari; Surabhi Sharma (Journal of Health Technology Assessment in Midwifery, 2021)
Backgrounds: Pregnancy is a normal physiological process experienced by women. During this COVID-19 pandemic, pregnant women have atypical experiences. The COVID-19 pandemic also instigates psychological problems in the form of anxiety and depression in pregnant women. Supports are exceedingly needed by pregnant women, especially during the current pandemic. They can take several measures during their pregnancy to reduce their level of anxiety.Objective of the study: To review evidence related to pregnant women’s experiences during the COVID-19 pandemic.Review methods: This scoping review method begins with identifying scoping review questions using PEO framework; identifying relevant articles chosen based on inclusion and exclusion criteria; searching for articles using databases, namely EBSCO, PubMed, Science Direct, and Wiley Online Library; selecting articles of which search flow is described through PRISMA Flowchart; performing data charting and critical appraisal; and compiling and reporting results.Results: Based on 8 chosen articles, 7 articles are marked grade A in quantitative research design non-randomized (5), quantitative descriptive (1), qualitative (1), and 1 article is marked grade B in quantitative descriptive research design. Furthermore, there are 3 obtained themes, including psychological conditions, coping strategies and the pregnant women's needs during the COVID-19 pandemic.  Conclusion: The COVID-19 pandemic affects the pregnant women’s experiences due to the emergence of psychological responses in the form of anxiety, depression and fear. One of coping strategies carried out by pregnant women during the COVID-19 pandemic is by doing physical activities such as exercising, doing their hobbies, thinking positively and finding out information. Social supports and accurate information obtained help pregnant women to overcome their anxiety.